2005
DOI: 10.5194/angeo-23-1281-2005
|View full text |Cite
|
Sign up to set email alerts
|

Survey of energetic O<Sup>+</sup> ions near the dayside mid-latitude magnetopause with Cluster

Abstract: Abstract. Since December 2000, the Cluster satellites have been conducting detailed measurements of the magnetospheric boundaries and have confirmed the unambiguous presence of ions of terrestrial origin (e.g. O + ) in regions adjacent to the dayside, mid-latitude magnetopause. In the present paper, we focus on the statistical properties of the O + ion component at energies ranging from 30 eV up to 40 keV, using three years of ion data at solar maximum from the Cluster Ion Spectrometry (CIS) experiment aboard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 40 publications
3
33
0
Order By: Relevance
“…Other studies that have shown a clear correlation between O + and geomagnetic activity are Peterson et al (2001), Cully et al (2003), and Kistler and Mouikis (2016). The O + density close to the mid-latitude magnetopause was shown by Bouhram et al (2005) to also increase exponentially with Kp. A consequence of increased ion outflow is an enhancement of the plasma feed into the plasma sheet during geomagnetic storms (Nose et al, 2005;Kistler et al, 2010;Haaland et al, 2012).…”
Section: Introductionmentioning
confidence: 88%
“…Other studies that have shown a clear correlation between O + and geomagnetic activity are Peterson et al (2001), Cully et al (2003), and Kistler and Mouikis (2016). The O + density close to the mid-latitude magnetopause was shown by Bouhram et al (2005) to also increase exponentially with Kp. A consequence of increased ion outflow is an enhancement of the plasma feed into the plasma sheet during geomagnetic storms (Nose et al, 2005;Kistler et al, 2010;Haaland et al, 2012).…”
Section: Introductionmentioning
confidence: 88%
“…Modulation of the O + density and energy by geomagnetic activity monitored by the Sym-H index was shown by Ohtani et al (2011). The O + density just inward of the magnetopause in the magnetospheric boundary layer also displays a significant exponential increase with geomagnetic activity indicated by the Dst index (Bouhram et al 2005).…”
Section: Plasma Sheetmentioning
confidence: 98%
“…This variability explains why O + can be the most abundant ion during specific periods in the midnight sector (Lennartsson and Shelley 1986;, in the near-Earth regions (e.g. Maggiolo and Kistler 2014) or in the dayside magnetosphere (Bouhram et al 2005) while if we consider the average plasma sheet composition H + is the dominant species (in number density) for all geomagnetic and solar activity level except at low geocentric distances near geostationary orbit .…”
Section: Plasma Sheetmentioning
confidence: 99%
See 2 more Smart Citations